2008
DOI: 10.1016/j.joca.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for articular cartilage regeneration in MRL/MpJ mice

Abstract: Male MRL/MpJ mice appear to possess an intrinsic ability to 'regenerate' articular cartilage. Understanding the biochemical and genetic basis for articular cartilage regeneration may open up new treatment options for traumatic articular cartilage defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
142
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(161 citation statements)
references
References 39 publications
16
142
2
1
Order By: Relevance
“…In support of previous studies [2,3], we found that at 4 weeks post-injury, repair in MRL mice was significantly superior to repair in C57 animals (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In support of previous studies [2,3], we found that at 4 weeks post-injury, repair in MRL mice was significantly superior to repair in C57 animals (Fig. 2).…”
Section: Discussionsupporting
confidence: 91%
“…After decalcification was completed, samples are washed with water and underwent tissue processing and embedding. Paraffin-embedded tissue sections at 7 μm thick were stained with Safranin-O and graded using a scoring matrix previously described [3].…”
Section: Histological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the wild type MRL/MpJ also displays a somewhat reduced level of autoimmunity. Further studies showed evidence of regeneration in many tissues including heart myocardium (Leferovich et al, 2001;Naseem et al, 2007;Alfaro et al, 2008), digit Chadwick et al, 2007), articular cartilage (Fitzgerald et al, 2008), cornea (Ueno et al, 2005) and peripheral nerves (Buckley et al, 2010). One specific type of injury in a given location, a flank or dorsal skin wound, has given mixed results.…”
Section: Introductionmentioning
confidence: 99%